2010
DOI: 10.1143/jjap.49.07he26
|View full text |Cite
|
Sign up to set email alerts
|

Design and Characteristics of Mode-Coupling LiNbO3 Ultrasonic Motor Depended on Width-to-Length Ratio of the Stator Vibrator

Abstract: A miniature ultrasonic motor fabricated from a LiNbO 3 rectangular plate was studied to improve its rotation characteristics. In this motor, the coupling modes of in-plane longitudinal and flexural modes caused by crystal anisotropy are used to realize a single-phase drive motor. The mode coupling vibrator is designed to have crystal cut angles and the width-to-length ratio W =L of the vibrator shape. In this study, we noted the new coupling condition of W =L % 0:84 compared with the conventional ratio of W =L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Bi-directional ultrasonic motors using mode coupling between the longitudinal and bending modes caused by the asymmetry shape (Aoyagi and Tomikawa, 1993; Aoyagi et al, 1992; Tamura et al, 2007) or crystal anisotropy (Tamura et al, 2008, 2010) of the stator were reported; the coupling effect could provide a pair of modes by asymmetry shape or crystal anisotropy; coupling mode is allotted to push the load in each direction; however, the output performances are not equal in each moving direction. Utilizing two same bending modes of a circle stator (Aoyagi et al, 2002; Takano et al, 1992, 1994, 1999), the same output performances in reverse direction were obtained; however, this type of structures was not suitable for effectively moving a linear slider directly.…”
Section: Working Principles and Configurationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bi-directional ultrasonic motors using mode coupling between the longitudinal and bending modes caused by the asymmetry shape (Aoyagi and Tomikawa, 1993; Aoyagi et al, 1992; Tamura et al, 2007) or crystal anisotropy (Tamura et al, 2008, 2010) of the stator were reported; the coupling effect could provide a pair of modes by asymmetry shape or crystal anisotropy; coupling mode is allotted to push the load in each direction; however, the output performances are not equal in each moving direction. Utilizing two same bending modes of a circle stator (Aoyagi et al, 2002; Takano et al, 1992, 1994, 1999), the same output performances in reverse direction were obtained; however, this type of structures was not suitable for effectively moving a linear slider directly.…”
Section: Working Principles and Configurationsmentioning
confidence: 99%
“…The theory of two in-plane modes of a ring excited by a single-phase drive was discussed (Cagatay et al, 2003; Koc et al, 2000, 2002; Peter, 1987; Sashida, 1982; Ueha et al, 1993). Tubular ultrasonic motors utilizing only one drive signal were developed (Aoyagi et al, 2002; Cagatay et al, 2003; Chen et al, 2015; Friend et al, 2003; Ishii et al, 1993; Koc et al, 2000, 2002; Ma et al, 2016; Takano et al, 1992, 1994, 1999; Tamura et al, 2010; Ueha et al, 1993); This motor has two orthogonal degenerative bending modes, and only one excitation signal was supplied to one PZT element at a frequency between the resonance frequencies of the two modes, activating both modes and providing oscillating movement. The rotation direction could be reversed by changing the voltage to the other PZT element.…”
Section: Working Principles and Configurationsmentioning
confidence: 99%
“…Typical studies of the single-phase driving-type USM were proposed using the L 1 mode of a piezo-laminated rectangular plate for application to watches and a microfan, 14,15) and provided thin miniature constructions and good characteristics; however, this type of USM cannot be rotated in the reverse direction. The single-phase-driven bidirectional USMs were reported using mode coupling between the L 1 and F 2 modes caused by the asymmetry shape [16][17][18][19] or crystal anisotropy 20,21) of the resonators. The coupling effect provides a pair of coupling modes.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasonic motors have several advanced characteristics such as small size, a large holding torque without energy consumption, high resolution, and silence, because the driving force is caused by the piezoelectric vibration of a stator instead of electromagnetic interactions. [1][2][3][4][5] However, nonlinearity in the voltage-speed characteristics causes problems for precise control. Various control methods have been proposed to eliminate the nonlinearity.…”
Section: Introductionmentioning
confidence: 99%